Lehman on the brink of bankruptcy: A case about aggressive application of accounting standards - Caplan, D.; Dutta, Saurav; Marcinko, D. (American Accounting Association, 2012)
In September 2008, Lehman became the largest company in U.S. history to file for bankruptcy. Nine months earlier, Lehman had reported record revenue and earnings for 2007, and had started the year with a market capitalization of over $30 billion. Lehman's precipitous fall has been attributed to a high-risk business strategy and to aggressive interpretation of accounting rules. Lehman was both a victim of-and an important contributor to-the worst U.S. economic recession since the Great Depression, and the firm's accounting choices warrant scrutiny. This case is structured around collateralized short-term borrowings, commonly used by financial institutions, called repurchase agreements. Lehman modified the terms of the standard agreement and used an aggressive interpretation of SFAS No. 140 to account for these modified agreements as a sale of the collateral. These transactions, called Repo 105s, affected the firm's reported financial position. The case requires students to evaluate those effects, interpret financial ratios, critically read authoritative accounting literature, and consider important questions about auditors' responsibilities. Key issues include the relative merits of principles-based versus rules-based accounting standards, corporate governance, ethics, materiality, and whistleblowing.